Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.jot.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in component size between preoperative measurement, navigation and final implant in total knee replacement

Abstract: Summary Background One of the possible causes of dissatisfaction reported by many patients after total knee replacement (TKR) is the lack of agreement between component size and bone structure. To avoid this complication and facilitate the procedure, preoperative planning with digitized templates is recommended. Surgical navigation indicates the best position and the most adequate size of arthroplasty and may therefore replace preoperative radiographic measurement. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Comparing the results to those available in the literature for manual planning/templating, the size prediction accuracy of the tool was shown to be considerably better than the average reported across the 10 studies summarized by Hernández-Vaquero et al (2019) . This was also true when compared to studies that utilized CT data for manual templating ( Vaishya et al, 2018 ; Kobayashi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Comparing the results to those available in the literature for manual planning/templating, the size prediction accuracy of the tool was shown to be considerably better than the average reported across the 10 studies summarized by Hernández-Vaquero et al (2019) . This was also true when compared to studies that utilized CT data for manual templating ( Vaishya et al, 2018 ; Kobayashi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 76%
“…Despite the importance of achieving a good fit, the accuracy of manual X-ray assessment and templating, for both femur components and tibia plates, can be poor. Hernández-Vaquero et al (2019) summarized the reported accuracies from 10 different studies and found mean selection accuracies of 59.2% for femur components and 60.7% for tibia plates. With ±1 size permitted, mean scores of 97.4% and 96.4% were recorded respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies that investigating the value and clinical role of preoperative templating, statistical modelling has assessed the success of the templated size in precisely matching the applied size, as well as the success of sizes one size larger and smaller than the templated size in matching the applied implant size. 5,11,16,30,31 While we also presented this data, it was not the primary focus of our statistical approach.…”
Section: Discussionmentioning
confidence: 99%
“…El resultado del eje mecánico obtenido en nuestros pacientes coincide con los resultados de varios metaanálisis, 14 proponiendo esta técnica de elección en deformidades en varo o valgo mayores de 10 o para aumentar la precisión del eje mecánico final y el posicionamiento de los componentes protésicos de tibia y fémur. 15,16 En nuestro estudio no incluimos los valores preoperatorios del eje mecánico para hacer una comparación objetiva, sólo pudimos comprobar que al utilizar esta técnica existen mejorías significativas tanto en funcionalidad, dolor y alineación del eje mecánico a mediano y largo plazo. Consideramos la necesidad de seguir a los pacientes por un período más largo para poder emitir resultados a largo plazo.…”
Section: Discussionunclassified